Kontrol Sosial Orang Tua Terhadap Penggunaan Smartphone Pada Anak Remaja - Rahmania, Indah; Nasir, Badruddin (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/ Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
Explores parents' social control over smartphone use among teenagers in Tasuk Village, and assesses the positive and negative impacts of smartphone use. Through a descriptive qualitative approach, this study reveals that the social control exercised by parents is classified into preventive and repressive categories. Preventive social control is carried out before deviations occur, such as supervision, time restrictions, and advice to children, while repressive social control is carried out after deviations occur, such as giving punishment or confiscating smartphones. The results show that these control efforts are generally quite effective in reducing the use of smartphones by teenagers. The positive impacts of smartphone use include making it easier to find information, communication, expanding friendship networks, and as an entertainment medium. However, there are also negative impacts such as self-closing, health problems, consumptive behavior, decreased concentration, and cyberbullying crimes.